(untitled) (Swiss Medical Weekly, 2018)
BACKGROUND Antimicrobial resistance data from surveillance networks are frequently do not accurately predict resistance patterns of urinary tract infections at the bedside. OBJECTIVE To determine simple patient- and institution-related risk factors affecting antimicrobial resistance patterns of Escherichia coli urine isolates. METHODS From January 2012 to May 2015 all consecutive urine samples with significant growth of E. coli (≥103 CFU/ml) obtained from a tertiary care hospital were analysed for antimicrobial susceptibility and related to basic clinical data such a patient age, ward, sample type (catheter vs non-catheter urine). RESULTS Antimicrobial susceptibility testing was available for 5246 E. coli urine isolates from 4870 patients. E. coli was most commonly resistant to amoxicillin (43.1%), cotrimoxazole (24.5%) and ciprofloxacin (17.4%). Resistance rates were low for meropenem (0.0%), fosfomycin (0.9%) and nitrofurantoin (1.5%). Significantly higher rates of resistance to ciprofloxacin (32.8 vs 15.8%) and cotrimoxazole (30.6 vs 23.9%) were found in urological patients compared with patients on other wards (p <0.01). In multivariable analysis, predictors for E. coli resistance against ciprofloxacin and cotrimoxazole were: treatment in the urological unit (odds ratio [OR] 2.04, 95% confidence interval [CI] 1.63–2.54; p <0.001 and OR 1.33, 95% CI 1.07–1.64; p = 0.010, respectively), male sex (OR 1.93, 95% CI 1.630–2.29; p <0.001 and OR 1.22, 95% CI 1.22-1.04; p = 0.015), and only to a lesser extent urine samples obtained from indwelling catheters (OR 1.30, 95% CI 1.05–1.61; p = 0.014 and OR 1.26, 95% CI 1.04–1.53; p = 0.020). Age ≥65 years was associated with higher resistance to ciprofloxacin (OR 1.42, 95% CI 1.21–1.67; p <0.001), but lower resistance to cotrimoxazole (OR 0.76, 95% CI 0.67-0.86; p <0.001). CONCLUSIONS Simple bedside patient data such as age, sex and treating hospital unit help to predict antimicrobial resistance and can improve the empirical treatment of urinary tract infections.